Analisis Penggunaan Teknologi pada Proses Pembelajaran di TK Aisyiyah Bustanul Athfal Jatibarang - Sisca Septiani; Wiwik Hidayati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Technology has become an important component in transforming education in the digital era, including at the early childhood education level, such as at Aisyiyah Bustanul Athfal Jatibarang Kindergarten. This study analyzes the application of technology in the learning process by focusing on the use of hardware (laptops/computers, LCDs, smartphones, speakers) and software (Canva, YouTube) in three stages of learning: planning, implementation, and evaluation. Using a qualitative narrative approach, data were collected through in-depth interviews and observations of the principal, teachers, and direct observation of student activities during the learning process. The study results indicate that integrating technology significantly improves the quality of learning by facilitating teachers in preparing materials, presenting educational content, and conducting learning evaluations. Although it positively impacts children's motivation and understanding, there are challenges in the risk of dependence on technology and suboptimal infrastructure, particularly limited WiFi access. Implications: The development of educational technology in kindergartens requires a balanced approach between technology and conventional learning methods, supported by improving teachers' digital competencies and infrastructure.